Pa Joad shows the handbill - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
Pa Joad shows the handbill, Illustration from the Grapes of Wrath, v.1, p.234, illustrated edition by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "Pa reached into his pocket and brought out the folded handbill" "Look,' said the man, 'Not till you see the fella that put out this here bill...Maybe he need two hundred men, so he talks to five hundred... The more fellas he can get, an' the hungrier, less he's gonna pay."